2010
DOI: 10.1161/circulationaha.109.882704
|View full text |Cite
|
Sign up to set email alerts
|

CD137 (4–1BB) Deficiency Reduces Atherosclerosis in Hyperlipidemic Mice

Abstract: Background— The tumor necrosis factor receptor superfamily, which includes CD40, LIGHT, and OX40, plays important roles in atherosclerosis. CD137 (4-1BB), a member of the tumor necrosis factor receptor superfamily, has been reported to be expressed in human atherosclerotic lesions. However, limited information is available on the precise role of CD137 in atherosclerosis and the effects of blocking CD137/CD137 ligand signaling on lesion formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
106
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 39 publications
(37 reference statements)
1
106
0
Order By: Relevance
“…As described below, CD137L signaling in non-hematopoietic cells is essential for tissue inflammation (Jeon et al, 2010;Kim et al, 2012a). Epithelial cells are the cells most commonly damaged by intracellular and extracellular insults, and therefore often initiate inflammation (Swamy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described below, CD137L signaling in non-hematopoietic cells is essential for tissue inflammation (Jeon et al, 2010;Kim et al, 2012a). Epithelial cells are the cells most commonly damaged by intracellular and extracellular insults, and therefore often initiate inflammation (Swamy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In renal ischemia-reperfusion injury, CD137L signals are required to recruit neutrophils (Kim et al, 2012a). The endothelial cells of vessels in atherosclerotic lesions express both CD137 and CD137L (Jeon et al, 2010;Olofsson et al, 2008). Since CD137 and CD137L signals can promote leukocyte transmigration by inducing pro-inflammatory cytokines and chemokines and by upregulating cell adhesion molecules in endothelial cells (Jeon et al, 2010), endothelial cells seem to activate either CD137-or CD137L-expressing leukocytes during transmigration into inflammation sites.…”
Section: Introductionmentioning
confidence: 99%
“…CD137 is expressed by various immune cells, such as activated CD4+ and CD8+ T lymphocytes, natural killer (NK) cells, CD4+CD25+ regulatory T cells (Treg), monocytes, neutrophils, mast cells, eosinophils, and dendritic cells9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 as well as nonimmune cells such as endothelial cells and vascular smooth muscle cells 10. The ligand of CD137 (CD137L) is primarily expressed on antigen‐presenting cells (dendritic cells, monocytes/macrophages, and B cells), human primary T cells22 and cardiac myocytes in myocarditis and aortic tissue in arteritis 23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that plasma sCD137 levels tended to decrease following treatment, in parallel with the decreasing serum MMP‐9 levels after statin therapy 42, 43. Unlike membrane‐bound CD137 that delivers a potent stimulatory signal to activate T cells, sCD137 may enhance immune responses by reverse signaling, as shown in an ex vivo study by Jeon et al ., who showed that sCD137‐treated macrophages expressing CD137L can produce MCP‐1 and TNF‐α 11. Taking our additional results into consideration, i.e., the positive correlation of sCD137 levels with brain infarct volume and disease severity, the shedding of CD137 from lymphocytes, such as activated CD4+ T cells, may function as a positive feedback mechanism to further promote brain ischemia‐related inflammation that has been triggered by the local cell–cell CD137/CD137L interaction in the acute stage of stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation